2002
DOI: 10.1086/338353
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Very Extended Emission‐Line Region around the Seyfert 2 Galaxy NGC 4388

Abstract: We found a very large, ∼ 35 kpc, emission-line region around the Seyfert type 2 galaxy NGC 4388, using deep narrow-band imaging with the prime focus camera (Suprime-Cam) of the Subaru telescope. This region consists of many faint gas clouds or filaments, and extends northeastwards from the galaxy. The typical Hα luminosity L(Hα) of the clouds is ∼ 10 37 erg s −1 , and the total L(Hα) of the region within 10 kpc from the nucleus is ∼ 2 × 10 38 erg s −1 , which corresponds to an ionized gas mass of ∼ 10 5 M . Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
125
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(137 citation statements)
references
References 49 publications
12
125
0
Order By: Relevance
“…The newly formed stars are mainly concentrated in the compressed residual disc. Like in the observations of Yoshida et al (2002Yoshida et al ( , 2004 some Hα emitting gas can be found several kpc behind the ram pressure affected disc in the forming gaseous wake.…”
Section: The Distribution Of the Different Componentssupporting
confidence: 70%
See 1 more Smart Citation
“…The newly formed stars are mainly concentrated in the compressed residual disc. Like in the observations of Yoshida et al (2002Yoshida et al ( , 2004 some Hα emitting gas can be found several kpc behind the ram pressure affected disc in the forming gaseous wake.…”
Section: The Distribution Of the Different Componentssupporting
confidence: 70%
“…They conclude that the most plausible formation mechanism for these star forming regions is ram-pressure stripping. Another example how ram pressure stripping influences the gaseous disc and the stripped material is presented in Yoshida et al (2004Yoshida et al ( , 2002. They investigated NGC 4388, a Seyfert 2 Virgo cluster galaxy, with deep optical spectroscopy.…”
Section: Comparison With Observationsmentioning
confidence: 99%
“…The galaxy is one of the most HI-deficient in our sample (def HI = 1.16), showing HI distribution truncated within the optical disk (Chung et al 2009a). Yoshida et al (2002) found that the Hα emission extends for 35 kpc in the north east direction. Vollmer & Huchtmeier (2003) found HI gas out to 20 kpc along the same direction as the Hα emission.…”
Section: Appendix A: Notes On Individual Objectsmentioning
confidence: 60%
“…By observing the galaxy in Hα Veilleux et al (1999b) found a large plume of ionized gas extending 4 kpc above the plane. In subsequent SUBARU observations Yoshida et al (2002) reveal a more extended tail out to 35 kpc to the northeast. Vollmer & Huchtmeier (2003) performed 21-cm line observations with the Effelsberg 100-m radio telescope.…”
Section: Introductionmentioning
confidence: 86%